Effects of the development of production factors on productivity - Vántus, András (Acta Agraria Debreceniensis, 2015)
In every economic sector, the enacted and expected quality of the products strongly affects its market entry and subsistence. The aim of management is success, competitiveness and subsistence that require adequate human and material resources and enough production stock. We must also notice that the quality of tools and instruments significantly influences work productivity. This applies to both plant production and animal husbandry.The author researched milk production factors with methodical observation, document analysis and interviews. Data were collected with a ten-year interval, thus this assay can highlight the field, volume and sources of investments during this period and that the production stock increased in most farms and decreased in few. The data also shows the influence of investments on work productivity - there are differences between farms of equal size, so there are still ways of development.